2020
DOI: 10.1002/ptr.6719
|View full text |Cite
|
Sign up to set email alerts
|

Natural product corynoline suppresses melanoma cell growth through inducing oxidative stress

Abstract: Natural product corynoline is a unique isoquinoline alkaloid extracted from traditional Chinese medicine Corydalis bungeana Turcz, whereas its anticancer properties have not been investigated. In this study, we found that corynoline potently impairs the growth of melanoma cells, B16F10, and A375 in a concentration-dependent manner. Treatment of melanoma cells with corynoline results in G2 cell arrest accompanied by reduced cdc2 activation. Furthermore, corynoline triggers apoptosis of melanoma cells, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Although several new drugs have been developed over the last 10 years that have greatly improved the prognosis of patients with metastatic melanoma, many patients do not show a lasting response to these treatments [ 5 ]. Treatment with natural compounds and preparations based on plant materials have been increasingly used among patients with various neoplasms [ 6 , 7 , 8 ], and natural product-based treatments for melanoma are constantly being researched [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although several new drugs have been developed over the last 10 years that have greatly improved the prognosis of patients with metastatic melanoma, many patients do not show a lasting response to these treatments [ 5 ]. Treatment with natural compounds and preparations based on plant materials have been increasingly used among patients with various neoplasms [ 6 , 7 , 8 ], and natural product-based treatments for melanoma are constantly being researched [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some therapeutic options already exist for melanoma, but their effectiveness is still limited, mainly due to acquired resistance [ 55 ]. Thus, the investigation of propolis activity in this type of cancer is important due to the need for new treatments and sources of therapeutic agents [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acetyldihydrosanguinarine (24), 6-ketenesanguinarine (25), and demethylsanguinarine (26) (Figure 8) are isolated from Corydalis bungeana Turcz. Xiyun Ye et al [62] determined the cytotoxic activity of the above two compounds against A549, HT-29, kb16, and P-388 cell lines, respectively, and their ED50 (µg/mL) values reach 1.840, 1.600, 0.340, and 0.051, respectively. Havelek R. et al [61] have indicated that homochelidonine (23) (Figure 8) induces apoptosis and arrests the G2 phase mitotic cell cycle in cancer cells, and 20 µM homochelidonine (23) inhibits the cell growth of SK-BR-3, HepG2, and MCF-7 by over 50%.…”
Section: Antitumor Activities Of Benzophenanthridine Alkaloids From C...mentioning
confidence: 99%
“…Acetyldihydrosanguinarine (24), 6-ketenesanguinarine (25), and demethylsanguinarine (26) (Figure 8) are isolated from Corydalis bungeana Turcz. Xiyun Ye et al [62] determined the cytotoxic activity of the above two compounds against A549, HT-29, kb16, and P-388 cell lines, respectively, and their ED50 (µg/mL) values reach 1.840, 1.600, 0.340, and 0.051, respectively.…”
Section: Antitumor Activities Of Benzophenanthridine Alkaloids From C...mentioning
confidence: 99%
See 1 more Smart Citation